2003
DOI: 10.1128/aac.47.1.174-180.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of 7-Substituted 9-Chloro and 9-Amino-2-Methoxyacridines and Their Bis- and Tetra-Acridine Complexes against Leishmania infantum

Abstract: 9-Chloro and 9-amino-2-methoxyacridines bearing different substituents in position 7, as well as their corresponding unsubstituted dimeric and tetrameric complexes, were investigated for in vitro antiproliferative properties against Leishmania infantum compared to toxicity towards human monocytes. The results clearly confirmed that several compounds of the 2-methoxyacridine series, together with their corresponding dimeric and tetrameric derivatives, had strong in vitro antiparasitic properties. Antileishmania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 31 publications
(36 reference statements)
0
29
0
Order By: Relevance
“…Comparison of the activity of EC with that of other compounds indicates the antileishmanial potential of the natural product tested. This activity seems superior to that observed for the antiulcer agent omeprazole against different leishmanial species (27), similar to that demonstrated for some naphthoquinones and ␥-pyrones (27,28), and inferior to that determined for aphidicolin derivatives, aromatic dications, some tetra-acridine complexes, and an essential oil from the leaves of Croton cajucara (4,15,29,43). The mechanism of killing is still a matter of debate; promastigote damage by EC was irreversible, suggesting fatal metabolic injury.…”
Section: Discussionmentioning
confidence: 86%
“…Comparison of the activity of EC with that of other compounds indicates the antileishmanial potential of the natural product tested. This activity seems superior to that observed for the antiulcer agent omeprazole against different leishmanial species (27), similar to that demonstrated for some naphthoquinones and ␥-pyrones (27,28), and inferior to that determined for aphidicolin derivatives, aromatic dications, some tetra-acridine complexes, and an essential oil from the leaves of Croton cajucara (4,15,29,43). The mechanism of killing is still a matter of debate; promastigote damage by EC was irreversible, suggesting fatal metabolic injury.…”
Section: Discussionmentioning
confidence: 86%
“…[63][64][65][66][67][68][69] Antituberculosis activity were predicted for our compound set 5-20 within the range of 0.364<Pa<0.684. Although no direct correlation were observed between Pa values and MIC values, it was notable that most active three compounds had good Pa scores (Pa>0.5).…”
Section: )mentioning
confidence: 99%
“…Additional evidence that the quinoline and 9-aminoacridine hits identified in the ELEC system are particularly good leads for further development is based on previous studies of these compounds as potential antimalarial compounds. Here it was shown that these relatively basic compounds with high LogP (lipophilicity) values favor their intracellular transport, which is responsible for the observed activity and selectivity (54)(55)(56)(57). Furthermore, it has been demonstrated that certain acridines (54,(58)(59)(60)(61) can inhibit DNA synthesis in Leishmania and/or Plasmodium, interfering with DNA transcription (topoisomerase II).…”
Section: Discussionmentioning
confidence: 99%